2007
DOI: 10.1002/bio.962
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ibuprofen in pharmaceutical formulations using time‐resolved terbium‐sensitized luminescence

Abstract: A sensitive and specific luminescence method for the determination of ibuprofen (IB) in pharmaceutical formulations in aqueous solution is described. The method is based on the luminescence sensitization of terbium (Tb(3+)) by formation of ternary complex with IB in the presence of tri-n-octylphosphine oxide (TOPO) and Tween-20 as surfactant. The luminescence signal for Tb-IB-TOPO is monitored at lambda(ex) = 229 nm and lambda(em) = 545 nm. Optimum conditions for the formation of the complex in aqueous system,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 42 publications
(22 reference statements)
4
11
0
Order By: Relevance
“…This method does not involve any pretreatment (except filtration). Complex formationextraction or centrifugation steps are required with other instrumental methods [17][18][19]22,24,26].…”
Section: *Uv Spectrophotometrymentioning
confidence: 99%
See 1 more Smart Citation
“…This method does not involve any pretreatment (except filtration). Complex formationextraction or centrifugation steps are required with other instrumental methods [17][18][19]22,24,26].…”
Section: *Uv Spectrophotometrymentioning
confidence: 99%
“…The various methods include the use of spectrophotometry [15][16][17], spectrofluorimetry [18][19], high-performance liquid chromatography (HPLC) with UV detection [20], HPLC-ELSD (evaporative light scattering detection) [21], HPLC [22], potentiometric titration [23,24], conductometric titration [24], capillary electrophoresis [25], and luminescence [26].…”
Section: Introductionmentioning
confidence: 99%
“…[23] Ibuprofen, which also has an α,β-diketonates group, was reported to form a complex with terbium and was determined by sensitized fluorescence. [24] In this work, it was found that the formation of europium(III)-naproxen complex significantly enhanced the weak CL of KIO 4 -H 2 O 2 reaction. [25] Based on these observations, the experimental conditions that affected the CL reaction were carefully optimized using flow injection mode.…”
Section: Introductionmentioning
confidence: 95%
“…This phenomenon is called the “antenna effect” and such complexes are considered to be light conversion molecular devices because they are able to transform light absorbed by the ligand into light emitted by the ions via an intramolecular energy transfer process. As part of our ongoing interest on method development on drug analysis , we report a novel method for the assay of AM in pharmaceutical formulations and in biological fluids. The method is based on the luminescence enhancement and sensitization of terbium brought about by complexation with AM.…”
Section: Introductionmentioning
confidence: 99%